The Collaboration of Padang City Government in Managing Covid-19 Disaster through The Dynamic Governance Concept - Putri Febri Wialdi; Roni Ekha Putera; Ria Ariany; Edi Hasymi (Universitas Sebelas Maret, 2022)
The Covid-19 pandemic has caused changes in various lives, including the administration of government as a policymaker and public service. Changes and developments in policies issued or made by the government during a pandemic need to be seen from the perspective of dynamic governance. The concept of dynamic governance is defined as how various policies, institutions, and organizational structures are selected to be able to adapt to conditions that indicate uncertainty and rapid environmental change. It is hoped that these policies, institutions, and structures will be able to be relevant and effective in meeting the needs of the community in emergency and long-term conditions. The focus of the dynamic governance concept is the uncertain future factors (uncertain conditions) that affect decision-making components such as thinking again, thinking ahead, and thinking across. In addition, there is also a lever factor in the form of able people who are capable of human resources in developing the concept of dynamic governance. Where the existence of able people in the administration of the state, especially during times of a disaster, is very influential and must be considered. This study aims to describe how the application of the concept of dynamic governance in dealing with COVID-19 in the city of Padang. This study uses qualitative methods with data collection techniques through interviews and literature study. With the results of the research, there are still variables and indicators of dynamic governance theory that have not been fulfilled, namely coordination between institutions that collaborate. So it can be concluded that it is necessary to make improvements in coordination activities to achieve a dynamic government in solving the problems of the COVID-19 pandemic in the city of Padang.